Consumption Practices of Halal Products by Indonesian Muslims in Osaka Japan: A Phenomenological Study of Religion - Suherman , Eman; Alpyani, Putri (Universitas Airlangga, 2024)
Indonesia is one of the countries actively sending migrants to Japan. In 2021, 59,820 Indonesians were recorded as living in Japan, with an estimated 70—80% identifying as Muslim. This study aims to describe the dynamics of halal product consumption among Indonesian Muslims in Osaka, Japan, through the lens of religious phenomenology. Data were analyzed using a qualitative approach with survey and descriptive-analytical methods. Primary data were collected through questionnaires and structured interviews with 31 respondents and 8 informants residing in Osaka between November 2022 and May 2023. The findings reveal that halal consumption practices in Osaka exhibit complex religious dynamics, transcending mere textual compliance with Islamic law. Halal consumption reflects spiritual efforts involving emotional, cognitive, and multisensory reflection. Informants with high levels of religious adherence demonstrated profound commitment through proactive efforts to consume halal products. These activities also fostered social solidarity, extending the meaning of worship to a collective dimension. Informants with moderate levels of religious adherence displayed creative adaptation to challenges, such as balancing flexibility with halal principles in the context of limited access and information. Religious phenomenology reveals that halal consumption practices among Indonesian Muslims in Osaka are not only efforts to maintain religious identity but also reflections of the adaptation and negotiation of spiritual values within a predominantly non-Muslim environment.